Nonlinear Creep Model of Deep Gangue Backfilling Material and Time-Dependent Characteristics of Roof Deformation in Backfilling Mining - Peng Huang; Jixiong Zhang; Qi Zhang; Ntigurirwa Jean Damascene; Yuming Guo (Geofluids)
With the gradual increase in mining depth of coal resource exploitation, deep backfilling mining has effectively solved the impact of strong deep mine pressure and strong mining disturbances. However, after deep backfilling mining, the backfilling material is subjected to high stress for a long time, and its viscoelasticity has a significant impact on the roof control effect. This paper uses a large-scale bulk confinement test device to analyze the viscoelastic properties of gangue, establishes a high-precision fractional viscoelastic creep model, and identifies the gangue parameters. The established fractional viscoelastic model was used as the foundation model of the beam, and the roof model based on the fractional viscoelastic foundation was solved. The top deformation characteristics of elastic foundation and fractional foundation were compared and analyzed, and the time effect, viscoelastic effect, and order effect of the fractional order viscoelastic foundation beam were discussed. The results show that the viscosity of gangue increased under the action of deep high stress. As time increased, the roof deformation also increased. In order to more effectively control the long-term deformation of the roof, the viscosity coefficient of the backfilling material should be greater than 20 MPa. This research provides relevant guidance for the requirements of backfilling materials for deep backfilling mining and the prediction of long-term dynamic deformation of the roof in underground excavations.